2016
DOI: 10.1016/j.tet.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and opioid receptor binding of indium (III) and [111In]-labeled macrocyclic conjugates of diprenorphine: novel ligands designed for imaging studies of peripheral opioid receptors

Abstract: Radiolabeled diprenorphine (DPN) and analogs are widely used ligands for non-invasive brain imaging of opioid receptors. To develop complementary radioligands optimized for studies of the peripheral opioid receptors, we prepared a pair of hydrophilic DPN derivatives, conjugated to the macrocyclic chelator DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid), for complexation with trivalent metals. The non-radioactive indium (III) complexes, tethered to the C6-oxygen position of the DPN scaffold by 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Binding studies 4.7.1. Competition binding-Assays to establish opioid receptor affinities of nonradioactive peptides were performed using membranes prepared from frozen male Hartley guinea pig brains (μ, κ) or fresh CD-1 mouse brains (δ) as previously described [21,23,69]. Protein concentrations were measured by the bicinchoninic acid assay using BSA for calibration.…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation
“…Binding studies 4.7.1. Competition binding-Assays to establish opioid receptor affinities of nonradioactive peptides were performed using membranes prepared from frozen male Hartley guinea pig brains (μ, κ) or fresh CD-1 mouse brains (δ) as previously described [21,23,69]. Protein concentrations were measured by the bicinchoninic acid assay using BSA for calibration.…”
Section: 7mentioning
confidence: 99%
“…Hydrophilic [ 111 In]-labeled DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10tetraacetic acid) conjugates of the small molecule naltrindole (NTI) [21], as well as [ 64 Cu]labeled NOTA (1,4,7-triazacyclononane-1,4,7-triacetic acid) conjugates of the peptide H-Tyr-Tic-Phe-Phe-NH 2 (TIPP) [22], maintain high affinity for δ sites. Similarly, [ 111 In]labeled conjugates of diprenorphine [23] and [ 99m Tc]-labeled conjugates of naltrexone [24] are under investigation as universal (μ, δ, κ) opioid receptor radioligands.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple determinations should be made to ensure the findings are reproducible. Representative procedures are given in references [55] and [98,124] for lipophilic and hydrophilic radiotracers, respectively.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…[8] Recently, Lever et al reported the synthesis and opioid receptor binding properties of 111 In-labelled diprenorphine DOTA conjugates for imaging by means of single photon emission computer tomography (SPECT). [9] In the last two decades, comprehensive reviews [8,[10][11][12] have summarized the diversity of radiotracers available in the field of opioid receptor imaging.…”
Section: Introductionmentioning
confidence: 99%